PENILAIAN KONSUMEN TERHADAP PERAN APOTEK SEBAGAI TEMPAT PELAYANAN INFORMASI OBAT DI KABUPATEN KUDUS - Yance Anas; mohammad djatmiko; Aristya Nourwaqiana (Universitas Wahid Hasyim Semarang, 2014)
ABSTRACT Pharmacists in community pharmacy have a professional obligation to provide information on exact, safe and rational of drug use to the patient. The purpose of this study is to investigate the consumer’s assessment on the role of community pharmacy as a central of drug information services in all of pharmacy on Kudus regency. The study was performed through direct observation by using a questionnaire on consumers in all of pharmacy in Kudus regency. Respondent selection was determined by a combination of proportional random and accidental sampling. Data analysis performed including a compliance analysis using the Likert scale. Respondent’s answers were categorizing with a normal standard distribution. Cartesian diagram is used to determine the order of priority of the factors that affect consumer satisfaction. The results show that the majority of pharmacy consumers (61.03 %) are satisfies with the drug information services in community pharmacy. Level of concordance between consumer expectations and satisfaction in accepting drug information at community pharmacy are 90% - 99%. The consumer knowledge about the safety of medication use and their attitudes on the role of community pharmacists is quite high. They still doubt about the truth of drug information provided by pharmacist or pharmacist assistant. Consumers expect a guarantee of the truth and credibility of drug information provided by the pharmacist and pharmacist assistant in community pharmacy. Keywords : Drug information service, community pharmacy, consumer assessment